Level of ability and adherence to antiretroviral therapy medication and quality of life for PLHIV - Misutarno, Misutarno; Nursalam, Nursalam; Sukartini, Tintin; Priyantini, Diah (International Journal of Innovative Research and Scientific Studies, 2025)
The quality of life of people with human immunodeficiency virus (PLHIV) is one of the concerns in the world of health that must be resolved so that health status continues to improve. This study aimed to analyze the correlation between the level of ability and adherence to antiretroviral therapy medication and the quality of life for PLHIV. A quantitative survey with a cross-sectional approach was conducted in the Tulungagung AIDS Eradication Commission, East Java, Indonesia. The study was conducted between October and December 2022 to evaluate the Ability Level, Compliance with ART Consumption, and Quality of Life of PLHIV. A total of 60 PLHIV were recruited and agreed to give consent as research respondents. All respondents who agreed to sign the informed consent to participate in this study were then asked to complete a questionnaire about Ability Level, Compliance with ART Consumption, and Quality of Life. Spearman's rho was used to detect the correlation between ability level, ART adherence, and quality of life. The results of cross-tabulation between the patient's level of ability, ART adherence, and quality of life among PLHIV show that patients whose level of ability is good demonstrate a higher quality of life (p = 0.005). Likewise, with patient ART compliance, the better the compliance, the higher the quality of life (p = 0.010).